Compósitos de alginato como material inteligente, modulação de solubilidade e objeto de ensino - Cacuro, Thiago Aguiar (Universidade Federal de São Carlos, 2019)
Alginate is a nontoxic, biocompatible polymer, that is easily obtainable. It can form gels through crosslinking when in contact with bivalent metal ions (ionic alginate gel) or through intermolecular bonds by exposure to a pH smaller than its monomers pKa (acid alginate gel). In the first part of this work, coreshell composites in the form of beads, were developed. These beads are composed of a mixture of acid and ionic alginate gel, with a novel phenomenon to alginate beads, those beads open, when exposed to neutral pH. The composites were characterized and their application as a pH-controlled release device was tested. In the controlled release tests, the methylene blue dye was used as a model molecule. In the second part of this work, the modulation of sodium alginate solubility, was made by the addition of an ester group in the chemical structure of the alginate. After esterification, the ester group was functionalized by the addition of a thiol group as proof of concept. The addition of the ether group promoted a modulation of the alginate solubility, making it soluble in organic solvents. In the last part of this work, polymers were used as a teaching object. Practical experiments using polymers were planned and applied with students, exposing the practical class protocol, its application with graduate students and the pedagogical results of these experiments. The aim is to evaluate the effectiveness in the acquisition of knowledge and applicability in teaching of those protocols.
Alginate composites as smart material, solubility modulation and teaching object
Keywords: Alginato; Compósitos de Alginato; Modulação da solubilidade; Polímeros Inteligentes; Polímeros Como Objeto de Ensino; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS